Food imports and exchange rate: the application of dynamic cointegration framework - Aliyu, Alhaji Jibrilla; Ismail, Normaz Wana (Institute for Mathematical Research, Universiti Putra Malaysia, 2017)
This paper studies how exchange rate policy influences households’ consumption styles represented by food imports. We provide an empirical analysis based on the Malaysian annual data from 1980-2012. An autoregressive distributed lag model (ARDL) was utilized in interpreting long-run elasticities of food import demand as a cointegrating relation, and short-run dynamics was interpreted using ECM based on cointegrating regression of the ARDL technique. The robustness of ARDL results are verified using Dynamic OLS (DOLS) estimation technique. Our results, while providing evidence that food import demand in the country is fairly inelastic to both income growth and relative prices of food imports, also raise some important policy issues, particularly on the competitiveness of the country’s agricultural and food exports.